Response to lime and phosphorus of wheat genotypes with different tolerance to aluminium - Freitas, José Guilherme de; Cantarella, Heitor; Camargo, Carlos Eduardo de Oliveira; Filho, Antonio Wilson Penteado Ferreira; Junior, Armando Pettinelli; Ramos, Valdir Josue; Felicio, João Carlos (Pesquisa Agropecuaria Brasileira, 2000)
Field experiments were set up during nine years, in a low fertility, very acid Cambisol, with the objective of evaluating the response to lime and phosphorus of four wheat genotypes differing in tolerance to soil acidity. The experiments were carried out without irrigation, in randomized blocks with a split-split plot design, with four replications. The plots contained the three rates of limestone (0, 6.5, and 13 ton ha-1); the split-plots the rates of phosphorus (0, 30, and 90 kg ha-1 of P2O5), and the split-split plots the wheat varieties (IAC-5, IAC-24, IAC-60 and Anahuac). Lime was applied in the first year (1987) and reapplied in 1991; phosphorus was applied yearly. Wheat varieties tolerant to soil acidity (IAC-5 and IAC-60) were more responsive to limestone and phosphorus application and, even in soils with acidity partially neutralized, showed higher grain yields than the acid sensitive variety (Anahuac). Limestone and phosphorus caused a decrease in the straw:grain ratio because they increased the grain yield more than the vegetative growth. This ratio was lower and more stable with IAC-60. Genotypes IAC-5 and IAC-60 were the most efficient to use the applied phosphorus to produce grain. Yields of grain and straw, and plant size were usually more affected by phosphorus than by limestone application.